Exploring the Understanding and Practice of Differentiated Instruction among Mobilizer Teachers in Cimahi City - Asep Ahyar; Dede Trie Kurniawan; Yunus Abidin; Dede Margo Irianto (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2025)
This research examines the understanding and application of differentiated instruction by mobilizing teachers, focusing on learning readiness, student profiles, learning environments, content, process, product differentiation, assessment practices, and the challenges encountered. Differentiated instruction is vital as a student-centered approach to enhance learning effectiveness. The study employed a quantitative descriptive research method, with data collected through questionnaires distributed to 100 randomly selected teachers mobilizers in Cimahi City. To strengthen data accuracy, interviews were conducted with 5 participants. Data analysis involved content analysis through data reduction, presentation, and conclusion drawing. Findings indicate that the understanding and implementation of differentiated instruction in all focus areas are categorized as very good. Mobilizing teachers reported no significant obstacles in applying this approach. These findings were further corroborated by interviews, which revealed similar results regarding understanding, application, and challenges. Overall, this study highlights that mobilizing teachers possess a high level of expertise in implementing differentiated instruction effectively and overcoming related challenges. These results emphasize the critical role of mobilizing teachers in fostering effective, student-centered learning environments through differentiated instruction.